KEPUASAN KERJA SEBAGAI MEDIASI PENGARUH KESEJAHTERAAN PEGAWAI TERHADAP LOYALITAS - Karyati, Euis; Nurhasan, Rohimat (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the influence of employee well-being on employee loyalty, with job satisfaction as a mediating variable, in a banking institution in Garut. The research employs a quantitative approach with a verificative design. The total population of 74 employees was used as respondents through a census sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that employee well-being has a positive and significant effect on both job satisfaction and employee loyalty. Job satisfaction also has a positive and significant effect on employee loyalty. Furthermore, job satisfaction significantly mediates the relationship between employee well-being and employee loyalty. These findings suggest that improving employee well-being not only directly enhances loyalty but also indirectly through increased job satisfaction. Therefore, organizations should comprehensively manage employee well-being as a strategic effort to improve job satisfaction and strengthen employee loyalty sustainably.